"Aku mengandung": Meninjau pernyataan Batsyeba dalam 2 Samuel 11:5 melalui kajian teologi feminis - Pradita, Yola (KURIOS, 2024)
Something is fascinating about Bathsheba's passivity in 2 Samuel 11. She spoke and said, "I am Pregnant". This statement is important to review because it describes Bathsheba's feelings and actions, considering that she has often interpreted them with a negative label. The author is interested in examining this statement according to feminist theological studies by considering its socio-cultural, religious, and economic context. It employs a qualitative research technique with a descriptive approach. The research results show that Bathsheba's statement is the strength and courage of a woman who can "step outside" her zone. He is a victim, but his statement is a victory even though Batsyeba appeared as a woman who enters the messianic lineage. Â  Abstrak Ada hal yang menarik dari kepasifan Batsyeba dalam narasi 2 Samuel 11, ia berbicara dan mengatakan â€œAku Mengandungâ€. Pernyataan tersebut penting untuk ditinjau karena menggambarkan perasaan dan tindakan Batsyeba mengingat selama ini ia kerap diinterpretasikan dengan label negatif. Penulis tertarik ingin meninjau pernyataan ini menurut kajian teologi feminis dengan mempertimbangkan konteks sosial budaya, agama dan ekonomi yang melatarbelakanginya. Penelitian ini menggunakan penelitian kualitatif dengan metode deskriptif. Hasil penelitian menunjukkan bahwa pernyataan Batsyeba adalah sebuah kekuatan dan keberanian seorang perempuan yang mampu â€œmelangkah ke luarâ€ dari zonanya. Ia adalah korban tapi pernyataannya adalah kemenangan bahkan Batsyeba tampil sebagai seorang perempuan yang masuk ke dalam garis keturunan mesianik